Applied Aspect of Panchakarma and their Mechanism of Action in Urdhwajatru Gata-Roga (Disease of Eye, ENT, Orodental, Head and Scalp) (AYUSHDHARA, 2022)
The phrase “Swasthyasya Swasthya Rakshnam” represents, maintaining the health of a healthy person, prevention of disease and “Aaturasya Vikara Prasamanam”, which means curing the disease of ailing person. These are the main aim and objective of Ayurved. The Shalakyatantra, a part of Astanga Ayurved, deals with the disease above throat. It includes the disease and treatment of Netra, Karna, Nasa, Kantha, Mukha, Danta and Siro-Kapala Gata Roga. Sansamana (conservative), Samsodhana (Panchakarma) and the Shastra chikitsa (surgical procedures) are the essential treatment modalities followed to treat a disease. These are the basic treatment modalities, explained in the classical texts of Ayurved. Panchakarma is a branch Ayurveda, meant for the removal of vitiated Dosha, Mala or toxic part of body and balances Dosha-Dushya through, Vamana, Virechana, Nashya, Basti, Rakta Mokshyana etc. In the disease like Abhisyanda, Adhimantha Timira, Danta Nadi, Upakusha and Dusthapratishyaya, most of the Panchakarma therapies are indicated according to the severity of the disease. In practice the patient, who undergoes Panchakarma or Sodhana Chikitsa as Pradhana karma or Poorvakarma shows better result than the patient treated without Sodhanakarma. The patients, treated with Sodhanakarma recover faster than patient treated only with Shamana-chikitsa does. Therefore, increasing and mainstreaming the Panchakarma procedure in Shalakya Tantra will definitely provide an effective and satisfactory outcome in Urdhwajatrugata disorders.